The STATUS KEBERLANJUTAN EKOSISTEM MANGROVE DI WILAYAH PESISIR KECAMATAN MENDAHARA KABUPATEN TANJUNG JABUNG TIMUR: STATUS KEBERLANJUTAN EKOSISTEM MANGROVE DI WILAYAH PESISIR Suistanability Status Of The Mangrove Ecosystem - Merdania, Agiska Ayu (Brida Provinsi Jambi, 2025)
Mangrove ecosystem have a complex functions including ecological functions and economic, socio-cultural functions. This ecosystem has unique resources and is vulnerable to habitat degradation. Decreased habitat quality and area area usually occurs due to several factors. These factors can come from natural factors and human activity factors. Natural factors that affect habitat degradation include accretion, abrasion, and sedimentation. Habitat degradation factors that come from human activities include encroachment, illegal logging, coastal development, and the creation of ponds. The mangrove area on the coast of Mendahara District, East Tanjung Jabung Regency was identified as experiencing habitat degradation. The goals of this research are to assess the sustainability of the mangrove ecosystem in the coastal area of Mendahara District, East Tanjung Jabung Regency, and to conduct a leverage analysis on the sustainability of the mangrove ecosystem in the coastal area of Mendahara District, East Tanjung Jabung Regency. Four dimensions—environmental, economic, social, and institutional—are analyzed using the RAPFISH technique. It will be validated using the Monte Carlo approach in order to calculate the stress value and R2 value after it has been evaluated. The leverage analysis method is used to identify key characteristics. According to the analysis of this study, the mangrove ecosystem in the coastal region of Mendahara District, East Tanjung Jabung Regency, is reasonably sustainable in the institutional, ecological, and economic dimensions, but less so in the social dimension. The leverage analysis of 36 attributes revealed 7 sensitive attributes that have an impact on the sustainability of the mangrove ecosystem in the coastal region of Mendahara District, East Tanjung Jabung Regency. The seven sensitive features that were found are the diversity of fauna, changes in coastlines, the availability of government funds, government help, community management of mangroves, social conflict, and law enforcement.